BRImo product marketing communication strategy at Bank Rakyat Indonesia Watampone branch office - Marwan Tuasikal; Ramlawati Ramlawati; Budiandriani Budiandriani (Institute of Computer Science (IOCS), 2023)
This study explains the use of the BRImo digital application in meeting the needs of the community at PT BRI KC Watampone. The method used is qualitative research method. The type of research used is descriptive research. The results of the study are 1) In the procedure for using Mobile Banking, the use of services obtained by customers allows customers to access their bank accounts through the BRI Mobile Banking application on smartphones. In particular, mobile banking has a positive impact on banks, customers and cellular telephone operators. The positive impact for banks is to gain more customers and gain customer trust. For customers, getting more services from the bank because Mobile Banking will facilitate customers in conducting banking transactions; 2) Strategies to facilitate customer electronic transactions, namely increasing the number of users of the completeness of service products that are ready to offer strategic locations, friendliness and effectiveness of services and facilities that support consumer convenience make consumers and customers feel safe and comfortable and customers are more willing to try the products offered. The bank tries to promote its services and services both directly and indirectly; 3) BRI KC Watampone's communication strategy conducts direct acquisition using BRI KC Watampone employees and customers. All BRI employees are required to download BRImo and transact with BRImo. Marketers acquired BRImo products to core cooperation customers and existing customers. BRImo also acquires employees from agencies and / or companies that already have BRI KC Watampone as core cooperation customers of BRI KC Watampone.